Associations of the Healthy Beverage Index (HBI) and the risk of Breast Cancer (BrCa): a case–control study - Navideh Khodadadi; Mohammad Hassan Sohouli; Mojtaba Ghadiani; Hamid Rezvani; Mahdi Tabarraee; Hamid Reza Ahadi; Sina Salari; Hamide Rahmani Seraji (BMC Women's Health)
Abstract Background Breast cancer (BrCa) is one of the leading causes of cancer-related deaths. There are several factors for getting BrCa, including some changeable factors related to lifestyle like unhealthy dietary patterns, so modifying them can prevent one third of the complications and deaths caused by BrCa. Therefore, we decided to investigate the relationship between Healthy Beverage Index (HBI) and the risk of BrCa. Methods In this hospital-based case–control study, 253 patients with BrCa and 267 non-BrCa controls were enrolled. Food consumption was recorded to calculate the HBI score using a semi-quantitative Food Frequency Questionnaire (FFQ). Additionally, by using binary logistic regression analysis with adjustment for confounders, the relationship between HBI and the risk of BrCa were assessed. HBI was established by Duffey et al. and is used to evaluate the overall quality of beverage intake and identify changes in consumption. Results Mean ± SD of age and BMI of the study participants were 47.92 ± 10.33 years and 29.43 ± 5.51 kg/m2, respectively. Patients with BrCa considerably outperformed controls in terms of waist circumference (WC), age at first pregnancy, history of abortion, and number of children(Pvalue < 0.05). Compared with those in the lowest quartile of HBI, subjects in the highest quartile had higher intake of energy, carbohydrate, protein, fat, fiber, sodium, potassium, calcium, magnesium, zinc, vitamin C, E, B9, fruits, vegetables, fish and nut as well as lower BMI and WC (Pvalue < 0.05). After adjustment for potential confounders, individuals in highest compared to lowest quartile of HBI had significantly lower risk of BrCa for total population (odds ratio (OR): 0.40; 95% confidence interval (95%CI): 0.21–0.76, Pvalue < 0.05), premenopausal (OR: 0.38; 95% CI: 0.16–0.92, Pvalue = 0.013), and postmenopausal (OR: 0.27; 95% CI: 0.10–0.78, Pvalue = 0.023). Conclusion Findings of this study suggested that higher HBI score decreased the risk of BrCa. However, further investigation is needed.